Letrozole vs. Placebo Pretreatment in the Medical Management of First Trimester Missed Miscarriage: a Randomized Controlled Trial - Torky, Haitham A.; Marie, Heba; ElDesouky, ElSayed; Gebreel, Samy; Raslan, Osama; Moussa, Asem A.; Ahmad, Ali M.; Zain, Eman; Mohsen, Mohamed N. (Geburtshilfe und Frauenheilkunde, 2018)
Introduction Misoprostol is used for the medical management of miscarriage as it is more effective in the early stages of pregnancy. Letrozole has an anti-estrogen effect and is used for the pretreatment of miscarriage with misoprostol.Aim The aim of this study was compare the efficacy and safety of letrozole with placebo pretreatment in the medical management of first trimester missed miscarriage.Design This was a prospective randomized case-control study.Patients and Methods Four hundred and thirty-eight women were randomly divided into two groups of 219; the placebo group received placebo tablets twice daily for 3 days, followed by 800 micrograms of misoprostol vaginally on the fourth day of enrolment, while the letrozole group received letrozole 10 mg twice daily for three days followed by 800 micrograms misoprostol administered vaginally. Symptoms and side effects were recorded, and the women advised to return to hospital if they experienced severe pain or bleeding or intolerable side effects and to report to hospital for a check-up one week after misoprostol administration. Ultrasound was done seven days after misoprostol administration to monitor outcomes. Surgical evacuation was carried out if medical management failed.Results There were significant differences between the two groups, with better outcomes found for the letrozole group in terms of rates of complete miscarriage, onset of vaginal bleeding, and interval between induction and onset of expulsion (p < 0.001). A higher rate of nausea and vomiting was reported for the letrozole group (p = 0.002). Differences between groups with regard to pre- and post-termination hemoglobin levels, fever, severe pain and severe bleeding needing evacuation were not statistically significant.Conclusion Adding letrozole to misoprostol improves the success rate and decreases the interval between induction and expulsion in cases of first trimester miscarriage; however, nausea and vomiting is higher with letrozole.
Keywords: letrozole; first trimester miscarriage; medical management